The Influence of Competency, Communication, and Work Ethic on Employee Effectiveness at the North Sumatera Governor's Office (Case study at the North Sumatra Governor's Office) - Kristiani Simangunsong; Andre Fitriano; Vinta Hotma Rotua Manullang; Henny Pratiwi (Indonesian Journal of Business Analytics, 2026)
This investigation purposes to analyze the influence of competence, communication, and work ethic on employee effectiveness at the Governor’s Office of North Sumatra. The background of this research is based on the importance of human resource quality in achieving organizational goals, particularly in the public sector which requires effective and efficient public services. The study employed a quantitative approach by involving all administrative employees as respondents, and the data were analyzed utilizing multiple linear regression. The outcomes reveal that competence, communication, and work ethic each have a positive and significant impact on work effectiveness, both partially and simultaneously. This indicates that employee effectiveness is strongly affected by skills, knowledge, clear communication patterns, and a strong work ethic. These findings imply that management needs to prioritize competence development, establish effective communication, and foster a high work ethic to achieve optimal employee effectiveness